PEMANFAATAN FITUR LIVE STREAMING PADA PLATFORM E-COMMERCE UNTUK MENINGKATKAN PENJUALAN (STUDI KASUS: TIKTOK SHOP) - Annida Nuriska Utami; Siti Mariam; Sahrul Ramadan (PT. ABIG RIZKY PUBLISHER, 2025)
The rapid advancement of digital technology has significantly reshaped the e-commerce landscape, with one notable innovation being the integration of live streaming features that blend entertainment with interactive shopping experiences. This paper seeks to explore the influence of live streaming in enhancing consumer engagement and boosting the effectiveness of digital marketing strategies, focusing on TikTok Shop as the primary case study. Utilizing a literature review method, based on a range of scholarly sources and relevant data, the findings indicate that TikTok Shop has successfully developed a shoppertainment ecosystem that encourages impulse purchases. This is facilitated through real-time interaction, transparent product demonstrations, and time-limited promotional deals that create a sense of urgency. Moreover, the feature helps foster consumer trust and strengthens emotional connections between brands and their audiences. For Micro, Small, and Medium Enterprises (MSMEs), leveraging live streaming presents a forward-thinking and flexible strategy to broaden market reach and support sustainable business growth amid rising competition in the digital marketplace.